KAJIAN KESUBURAN DAN KESESUAIAN LAHAN BERBASIS KOMODITAS DI KECAMATAN TUGU DAN KARANGAN KABUPATEN TRENGGALEK - Arifin, Syamsul; Samudra, Ferdianto Budi; Utami, Kartika Budi; Putra, Aditya Nugraha; Setiawan, Adi; Riza, Sativandi; Andhika, Yosi; Maulidiyah, Nurul (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Drought is a major challenge in developing the integrated farming system (IFS) in Trenggalek Regency, making it one of the factors contributing to the construction of the Tugu Dam. Additionally, in developing the IFS area, it is necessary to assess soil fertility and land suitability evaluation for food and livestock feed commodities. The research was conducted in Tugu and Karangan Sub-Districts, Trenggalek Regency by conducting spatial analysis and soil survey at locations potentially affected by dam construction and soil samples analysis at the laboratory. The results of this study found that the level of soil fertility at the research site was included in the low to very low class with characteristics of acidic pH, very low C-organic, very low total N and low base saturation. While the results of the actual land suitability evaluation of rice, maize, and elephant grass showed the land suitability class S3 with limiting factors of C-organic, pH, total N, P2O5, and base saturation.